PENGARUH PENDEKATAN BELAJAR KOOPERATIF DAN BELAJAR KOMPETITIFSERTA KEMAMPUAN MOTORIK TERHADAP PENGEMBANGAN SELF-ESTEEM MELALUI KEGIATAN OLAHRAGA PERMAINAN PADA SISWASEKOLAH DASAR - Uhamisastra, - (2010)
The undevelopment of affective domain in education is coming rise. It was signed by trying suicede of elementary student that was caused by he wasn't given some money by his parents. A student refuse to eat just caused he got a low mathematic's grade. There is also student get sick suddenly to hide from physical education lesson. The students is afraid to take a participation in physical education activities, they afraid to swim, the girl student afraid that their hair become underlayer, their nail will broken down, their face skin will dark colour, or their hand will pain just caused playing volley ball game. All these reasoning will made lowest student's self esteem. To resolve this issue, an experiment design was conducted by using "nonequivalent comparison group design," by implementing cometitive and cooperative learning approaches as students in the experimental group. The subject consists of 80 fifth grade Elementary School students in Bandung. There is one self esteem test consisted of scholastic competence, athletic competence, social acceptance, physical appearance, behavior conduct and self worth, which have also been develop by Kathleen Haywood. This instrument has been tested for both its validity and reliability. Result of the study indicated that cooperative learning and competitive learning approaches applied to low and high motor ability students resulted in significantly different self esteems of the groups of students. An interaction was also detected between learning approach and the students' motor ability. It is recommended that a cooperative learning approach should be implemented by physical eduation teachers in developing student's self esteem.